Anti-discrimination measures in education: A comparative policy analysis - Amanda Lenhardt; Ella Page; Moizza Binat Sarwar; Andrew W. Shepherd (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Efforts to tackle discrimination in access to basic services have shown mixed results in different country settings. This study examines the positive and negative outcomes attributed to anti-discrimination measures adopted in different country contexts and analyses the factors contributing to these outcomes, with a specific focus on anti-discrimination measures in education. An analysis of trends in inequalities in human development is used to identify three countries that have seen positive change in reducing inequalities and three countries that have seen negative change. This is followed by a literature review exploring the factors that have contributed to the changes observed in these six cases. We find that reductions in inequalities have been achieved in those countries where targeted measures have gone alongside universal measures, where the constitution is used to generate an equity-focused political discourse, and where evidence on exclusion from education has been taken up politically.
Keywords: I24; I32; D63; J15; H75; 330; inequality; anti-discrimination measures; poverty; education; public policy